2015
DOI: 10.1038/ncomms8877
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dynamic insights into the energetics of activation loop rearrangement in FGFR1 kinase

Abstract: Protein tyrosine kinases differ widely in their propensity to undergo rearrangements of the N-terminal Asp–Phe–Gly (DFG) motif of the activation loop, with some, including FGFR1 kinase, appearing refractory to this so-called ‘DFG flip'. Recent inhibitor-bound structures have unexpectedly revealed FGFR1 for the first time in a ‘DFG-out' state. Here we use conformationally selective inhibitors as chemical probes for interrogation of the structural and dynamic features that appear to govern the DFG flip in FGFR1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 66 publications
3
56
0
Order By: Relevance
“…1b). Our findings are also consistent with the presence of a “molecular brake” in an inactive state of FGFR KD and similar kinases52, a feature near the hinge region that could restrain two kinase lobes and also suppress the catalytically significant DFG flip in the A-loop by imposing a particularly high free-energy barrier20.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…1b). Our findings are also consistent with the presence of a “molecular brake” in an inactive state of FGFR KD and similar kinases52, a feature near the hinge region that could restrain two kinase lobes and also suppress the catalytically significant DFG flip in the A-loop by imposing a particularly high free-energy barrier20.…”
Section: Discussionsupporting
confidence: 87%
“…Experimental approaches to monitor the dynamic properties of protein kinases at high resolution have been based mainly on application of nuclear magnetic resonance (NMR)1415, however, this approach has been successfully applied only to a small number of protein kinases161718192021. Due to the difficulties in obtaining experimental data, molecular dynamics (MD) simulations have been performed more extensively, providing theoretical calculations and working models for dynamic behavior of kinases212223242526272829.…”
mentioning
confidence: 99%
“…; Klein et al . ); therefore, the conformational state of the P‐loop was considered not to affect the association of these two drugs with FGFR kinases. It has also been reported that dovitinib and ponatinib come into contact with the gatekeeper residue.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced affinity of the V561M mutant for PD173074 was caused not only by steric hindrance around the gatekeeper residues, but also by steric clash induced by the structural change around the P-loop region. Crystallographic analysis showed that dovitinib and ponatinib showed no appreciable contact with the Ploop (Lesca et al 2014;Tucker et al 2014;Bunney et al 2015;Klein et al 2015); therefore, the conformational state of the P-loop was considered not to affect the association of these two drugs with FGFR kinases. It has also been reported that dovitinib and ponatinib come into contact with the gatekeeper residue.…”
Section: Discussionmentioning
confidence: 99%
“…One such method that can resolve local (near amino acid) perturbations in stability in arbitrarily large proteins is hydrogen/deuterium-exchange mass spectrometry (HDX-MS) (11)(12)(13)(14)(15)(16). Moreover, these measurements are made in solution without the need to trap specific conformers, which has been used to answer questions of epitope mapping (17), protein-drug binding (18), protein-protein interactions (19), aggregation (20), effects of mutation (12), and allosteric regulation (21).…”
Section: Introductionmentioning
confidence: 99%